Becoming the Flute: Socrates and the Reversal of Values in Kierkegaard’s Later Work - Scopetea, Sophia (KIERKEGAARDIANA, 1996)
Becoming the Flute: Socrates and the Reversal of Values in Kierkegaard’s Later Work